Organizational health in healthcare organizations – psychometric validation of the Healthcare-OH survey across fifteen acute NHS trusts in England. (2nd October 2021) - Williams, Stephen P.; Nicolay, Christopher R.; Purkayastha, Sanjay; Chaturvedi, Sankalp; Darzi, Ara
ABSTRACT: Healthcare-OH is the only healthcare-specific measure of organizational health currently in use and for this concept to be truly applied in a healthcare context then reliable and valid measurement is essential. The primary focus of this study is to determine the dimensionality, reliability and so the construct validity of this measure, as applied to its target demographic. The Healthcare-OH survey was disseminated nationwide across acute NHS trusts in the UK. Survey dimensionality and construct validity was examined using confirmatory factor analysis. 5412 participants completed the survey from fifteen trusts covering the breadth of the country. Existing models had considered the Healthcare-OH survey as a series of sub-scales but attempts to fit these models resulted in both poor fit indices and low reliability estimates. An eight factor model, representing the entire 112-item survey, was then devised, with each domain of organizational health denoted as a separate factor. This model demonstrated both acceptable fit indices and a high level of reliability for all factors. We believe that in the future, organizational health measurements, if performed serially and on a large scale, could provide invaluable information for healthcare organizations on their relative strengths and weaknesses, unearthing previously unseen opportunities for targeted organizational change.